Associations between toxoplasmosis and rheumatoid arthritis among patients in Zakho City, Kurdistan Region/Iraq - Sultan Muhamad Mizuri , Sarwin; A. Ramadhan, Chira; Mero, Wijdan Mohammed Salih (Zanco Journal of Medical Sciences (ZJMS), 2024)
Background and objective: Toxoplasmosis is a zoonotic disease that can cause a wide spectrum of clinical diseases. This study aimed to investigate the association between toxoplasmosis and rheumatoid arthritis among patients, besides, to confirm the role of Toxoplasma gondii in the enhancement and modulation of autoimmune diseases such as rheumatoid arthritis. Methods: A cross-sectional study was implemented from August 2021 to February 2022, in which blood samples were taken conveniently from a total of 180 patients from both genders and different ages (15-60 years). These patients attended Zakho General Hospital and some private clinics suffering from symptoms related to rheumatoid arthritis. All samples were tested for Toxoplasma gondii immunoglobulins G and M (IgG, IgM) antibodies, C- reactive proteins (CRP), rheumatoid factor (RF), and erythrocyte sedimentation rate (ESR). Results: The total seropositivity of anti-Toxoplasma gondii IgG and IgM Abs using ELISA were 13.9% and 3.9%, respectively. Furthermore, the highest rate (16.4%) of IgGAbs was recorded among the male group, while, the highest rate (4.8%) of IgMAbs, was recorded among the female group. Furthermore, the highest rate of IgG, and IgM Abs were recorded among the age group 46-60 in both genders (20%, 5.7% respectively). In addition, the statistical analysis demonstrated the presence of significant relationship between IgG Abs with CRP and RF test results (P = 0.027, 0.039 respectively). Whereas, concerning ESR only seropositive IgM Abs results were statistically significant (P = 0.049). Conclusion: Toxoplasmosis may influence the immune system and act as a contributing factor in the exacerbation of autoimmune illnesses, including rheumatoid arthritis. Subsequent investigations will be essential to delineate the risks of T. gondii within the human population.